Pengaruh Aplikasi Biochar dan Mikroba Penyubur Tanah terhadap Produksi Tanaman Kacang Tanah pada Tanah Masam - Artsam, Andi Fiqri Aulia; Lukiwati, Dwi Retno; Budiyanto, Susilo (UNIVERSITAS LABUHANBATU, 2022)
Utilization of acidic marginal land for the cultivation of peanuts results in uneven yield productivity. Acidic soil is soil with a low base saturation level which affects the absorption of plant nutrients from the soil. This study aims to examine the effect of biochar and inoculation of soil-fertilizing microbes, Rhizobium sp. and arbuscular mycorrhizal fungi (AMF), also its interaction on groundnut production on acid soils. This experiment used a 4 Ã— 3 factorial experiment with a completely randomized design (CRD) which was repeated 3 times. The first factor was the type of biochar material which consists of no application or control (B0), corn cobs (B1), rice husks (B2), and coconut shells (B3). The second factor was the inoculation of soil-fertilizing microbes consisting of Rhizobium sp. (M1), arbuscular mycorrhizal fungi (AMF) (M2), and the combination of Rhizobium sp. + AMF (M3). The results showed that the application of biochar was significantly different to plant height, while the inoculation of soil-fertilizing microbes was significantly different to the number of leaves. Both showed no significant difference in the total weight of pods, seeds, soil pH, and the proportion of CMA colonization. Treatment of biochar from rice husk and double inoculation of Rhizobium sp. + CMA significantly obtains the highest yield in effective root nodule production.